The Physical–Digital Divide: Exploring the Social Gap Between Digital Natives and Physical Natives. (August 2019) - Ball, Christopher; Francis, Jessica; Huang, Kuo-Ting; Kadylak, Travis; Cotten, Shelia R.; Rikard, R. V.
Older adults are the most digitally divided demographic group. The present study explores how older adults perceive the physical use of information and communication technologies (ICTs), particularly across generations and contexts. Data for the present study come from nine focus groups. Seniors acknowledge that ICTs help them connect with geographically distant social ties, but that they lead to feelings of disconnection with geographically close social ties. We label this phenomenon the "physical–digital divide, " which exists when a group feels ostracized or offended when those around them engage with ICTs while they themselves are not or cannot engage with ICTs. Younger generations are often referred to as "digital natives" and older generations as "digital immigrants." A more apt label for older adults may be "physical natives, " as their preferred method of communication involves physical face-to-face interactions and traditional codes of etiquette. Suggestions are made for reducing the physical–digital divide.